Unexpected mechanism for glucose-primed soil organic carbon mineralization under an anaerobic–aerobic transition - Dunham-Cheatham, Sarrah M.; Zhao, Qian; Obrist, Daniel; Yang, Yu (Geoderma, 2020)
Top: Schematic diagram for the dominant pathways of indirect priming of soil organic carbon mineralization by glucose in soils that experience an anaerobic–aerobic transition. Bottom: results highlighting the correlation between reduction of Fe phases and mobilization of soil organic carbon in the presence of glucose with subsequent carbon mineralization when aerobic conditions return. [Display omitted] •Glucose increases reductive release of iron oxide-bound carbon under anaerobic conditions.•Released carbon positively primes soil organic carbon mineralization.•Priming effect is larger when glucose is added under anaerobic, not aerobic, conditions.•Results have implications for modeling CO2 fluxes from soils experiencing redox fluctuations. Redox reactions are important for cycling of carbon (C) in soils frequently subject to fluctuations in redox conditions, such as wetland soils, which contribute around one third of the global terrestrial C reservoir. Priming effects (PE), induction of changes in C mineralization due to additions of energy-rich organic carbon (OC) substrates, have been largely ignored during redox transitions in current modelling and experimental efforts for evaluating C cycles. In this study, we investigated the effects of glucose input on the mineralization of soil OC during an anaerobic–aerobic transition. Substantially more soil OC was mineralized under aerobic conditions in samples that received glucose under preceding anaerobic conditions compared to controls that did not receive glucose and to samples that received glucose under aerobic-only conditions. Our results reveal a novel PE by which glucose indirectly primes the mineralization of soil OC by increasing the reductive release of iron oxide-associated OC under anaerobic conditions, followed by a dramatic positive PE when aerobic conditions are reestablished. Inclusion of this novel indirect priming mechanism is crucial for accurately predicting the contribution of atmospheric greenhouse gases from soils experiencing redox fluctuations (e.g., wetlands).